STUDI KASUS PESERTA DIDIK YANG KURANG MANDIRI DALAM PEMBELAJARAN DARING - Pebrianti, Pebrianti (Jurnal Kajian Pembelajaran dan Keilmuan, 2022)
This study aimed to identify cases of students who were less independent in online learning in   Public Junior High School number 8 in Pontianak. A case study designemployed in this study was as a part of qualitative research.   The data were collected through classroom observation, interview and home visit. The participants of this study were two students of eight grade in one of the public junior high schools in Pontianak. The finding revealed that the factors causing students less independent in online learning were lack of motivation to learn, lack of responsibility to learn, limited internet quota, less conducive home environment and learning system, less attractive schools during online learning,   dependent, procrastination, unable to solve learning difficulties, and lack of confidence. To overcome the problems, the first research participant used a behavioral counseling model with assertive training technique and positive reinforcement. The second research participant  used a behavioral counseling model with modeling technique and intermittent reinforcement. However, in order to achieve maximum result from the treatment, it is suggested that the guidance and counseling teachers should know better on how to treat the students who experience learning difficulties during online learning.